MEMAHAMI NILAI PEMBERDAYAAN CREDIT UNION - Kunradus Kampo (SIMAK, 2020)
This research aims to explore the main meaning that became the core values of empowerment that done by Credit Union (CU). Through a case study approach on CUMK, the researcher then explores the values of CU in stages based on an economic perspective, a church perspective (ecclesia), and a biblical perspective. We found that the meaning of CU empowerment is very comprehensive and holistic that unite inclusive economic concept and the social teaching of the church and also the word of God on bible that focused on raise human dignity to live prosperous. Thus, we conclude that core values of CU empowerment is compassion. Personal human well-being as well as community welfare, should be developed, because man is the creator, center and destination of all social economic life. Whoever obeys to Christ, and first of all looking for Kingdom of God, will draw from Him compassion that stronger and clearer to help all brothers and sisters, and to be soulful of compassion carry out the opus of justice (Gaudium et Spes, 3: 63 and 72).